Radiographic assessment of the knee joint in osteoarthritis. Issue 1 (January 1992) - Cooper, C; Cushnaghan, J; Kirwan, J R; Dieppe, P A; Rogers, J; McAlindon, T; McCrae, F
Abstract : The development of radiographic systems for the grading of osteoarthritis requires knowledge of the reproducibility of their individual component features. This paper reports the reproducibility, both within and between observers, for five commonly used radiographic features of osteoarthritis in the tibiofemoral and patellofemoral compartments of the knee joint. The results suggest that assessments of joint space narrowing, osteophyte, and bony contour in the tibiofemoral compartments are more reproducible than those of sclerosis and cyst. Patellofemoral assessments, with the exception of osteophyte, are considerably less reproducible between observers than tibiofemoral assessments.